Buncher of electron linac-injector for a synchrotron - Chernov, K.N.; Logachev, P.V.; Ostreiko, G.N.; Serdobintsev, G.V.; Shiyankov, S.V.; Yasnov, G.I. (Вопросы атомной науки и техники, 1999)
The application of RF buncher-accelerators for obtaining the short electron bunches is rather known. Their design varies. Linear accelerators with high-current pulsed beams at energy more than 30 MeV are mainly used as injectors into synchrotrons at modern accelerating complexes. The beam should be previously prepared as series of bunches for injection to obtain stable and effective accelerating regime. In this case RF electron sources would be appropriate for use at the input of a linear accelerator. Such preparing the beam allows one to achieve an effective beam capture into the accelerating regime of linear accelerator for each of the bunches, as well as synchronized operation of the complex with decreased level of radiation background.